The Nexus of Cancer Patient Experiential Satisfaction on the Intention to Recommend - Harjono, Eko Ivan; Antonio, Ferdi (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
This research aims to test and analyze the relationship of antecedents of patient experience measured by the CPEQ (The Cancer Patient Experience Questionnaire) instrument which consists of service by ward nurse, service by specialist, service by ward doctor, information, and hospital staff coordination. Further its impact on the intention to recommend the respective private hospital. This research was accomplished with a quantitative survey and using a cross-sectional approach. Respondents were taken by purposive sampling who had been treated at a private special cancer hospital in Jakarta. A total of 192 respondents met the requirements and were analyzed using PLS-SEM. The results showed that the six antecedents have a significant and positive relationship with cancer patient experiential satisfaction and encouraging patient intention to recommend the hospital. The strongest relation was found in the service by specialist doctors followed by hospital standards, service by nurse wards, and information. The findings in this study establish the positive relation between cancer experiential satisfaction and the intention to recommend the hospital.